4 - Apartheid’s University: Notes on the Renewal of the Enlightenment - Lalu, Premesh (Journal of Higher Education in Africa, 2007)
This paper sets to work on strategies for forging new and critical humanities at the institutional site of the university that appears to be trapped in the legacies of apart- heid. The paper suggests that the university’s responses to apartheid might hold the key for the realignment of its critical commitments in the post-apartheid present. Rather than merely invoking the Enlightenment traditions of the modern university as sufficient grounds for proclaiming a post-apartheid reorientation, I track the career of notions of academic freedom and university autonomy in the outlines of complicity. I show how the concepts of academic freedom and autonomy obscured a prior contract with the state and how that complicity extended a process of sub- jection. By deploying the postcolonial strategy of ab-using the Enlightenment, the paper outlines the failure of opposing apartheid in the name of academic freedom and autonomy. That failure, I argue, resulted in an inability to investigate the relationship be- tween the university and the state and blinded the university to its role in the crea- tion of racial subjects. Rather than merely casting the university in terms of the foundational concepts of academic freedom and university autonomy, I suggest that it might be more productive to consider the epistemological and political potential of a renewed reference to the Enlightenment. Apartheid’s University, cast as conti- nuity of the Enlightenment legacy, might allow us to rewrite its abject script in the direction of resisting the forms of subjection supported by that process of normali- sation.